ANALYSIS OF SHORT-TERM VARIATION AND LONG-TERM DRIFT DURING REAGENT KIT LOT CHANGE IN AN NABL ACCREDITED CLINICAL BIOCHEMISTRY LABORATORY - Kandi, Sibin Madathan (Journal of Medical Biochemistry, 2020)
Background: Kit lot change in clinical biochemistry labs leads to variations in patient results. This study planned to identify variations during 60 reagent lot changes in our laboratory during the period from June 2018 to May 2019. Methods: A statistical analysis was performed to identify the difference between patient samples results variations and QC results. The long term drift was analyzed using a regression test. Results: There was a significant difference between the patient and QC results in 16.7% of reagent lot changes. Moreover, the extent of variation in QC results was 3.3%. No long-term drift was seen in three analytes which were studied using regression analysis. Conclusions: Our results showed that, during reagent kit lot change, along with QC material, the patient samples should also be run in order to identify the variation. However, this practice is presently ignored by most of the laboratories. There was no accumulated effect in our laboratory due to reagent kit lot change.